Telesna dejavnost oseb z okvaro hrbtenjače po odpustu s primarne rehabilitacije - Žen Jurančič, Marijana (Rehabilitacija (Ljubljana), 2016)
Background: The level of cardiorespiratory fitness in persons with spinal cord injury is low. Beside specific atherogenic in morphologic changes after spinal cord injury, it is the major risk factor for cardiovascular disease. The aim of our study was to analyse cardiorespiratory capacity after discharge from primary rehabilitation and in home environment. Methods: Cardiorespiratory capacity of persons with spinal lesion was measured at the end of primary rehabilitation and during the first follow-up visit in the outpatient clinic. We performed exercise testing on a manual cycle ergometer according to the standard protocol. An interview was also conducted with each participant. Results: During the follow-up test, we confirmed improvement of cardiorespiratory capacity only in the group with high-level lesion. There were no statistically significant differences in the measured maximum blood pressure and heart rate. Only two patients followed the recommendations for exercise in the home environment. Conclusions: Persons with spinal cord injury should be encouraged to be more physically active in their home environment. This would also lead to increase independence in activities of daily living. They need an individual workout plan and support from the local paraplegic association.
Keywords: cardiorespiratory capacity; Exercise; Exercise test; kardiorespiratorna zmogljivost; obremenitveno testiranje; okvara hrbtenjače; Spinal cord injuries; telesna vadba